Dynamic analysis of drag torque for spur gear pairs considering the double-sided films. (June 2017) - Liu, Fuhao
Taking into account different drag torque, this paper investigates the influence of the lubricant films located in the backlash between meshing gear teeth pair on the gear dynamical behaviors. Numerical simulations show that the influence of the lubricant film on the coast side is significant under low loading, but under increased drag torques the influence is diminished. The shape of the hysteresis loop of double-sided films suggests that this model can make more sense. The sensitive of the drag torque is studied to illustrate the inverse relationship between drag torque and gear rattle: increased drag torque loading will increase to possibility of metal–metal contact which could generate noise, while decreased drag torque loading can promote noise due to rattle.